External habits formation and the environment - Fatma Safi (Naše gospodarstvo / Our Economy, 2021)
The present paper presents a standard overlapping generations model with external habits formation and environmental quality in the utility function. Our main objective is to study the impact of external habits on capital accumulation and environmental quality on the intertemporal competitive equilibrium. We notice that striving for status leads to environment worsening and capital increasing when the cohort size is large.
Keywords: D62; D91; E21; Q50; 330; external habits; overlapping generations; environmental quality